Imperative Objects and Mobile Processes - Kleist, Josva; Sangiorgi, Davide (BRICS Report Series, 1998)
An interpretation of Abadi and Cardelli’s first-order Imperative Object Calculus into a typed pi-calculus is presented. The interpretation validates the subtyping relation and the typing judgements of the Object Calculus, and is computationally adequate. The proof of computational adequacy makes use of (a pi-calculus version) of ready simulation, and of a factorisation of the interpretation into a functional part and a very simple imperative part. The interpretation can be used to compare and contrast the Imperative and the Functional Object Calculi, and to prove properties about them, within a unified framework.